Effectiveness of virtual reality for functional disorders in cerebral palsy: an overview of systematic reviews and meta-analyses - Fang, Enhui; Guan, Hui; Du, Binhong; Ma, Xuejun; Ma, Lihong (Frontiers in Neurology, 2025)
ObjectiveCerebral palsy (CP), a pediatric neuromotor disorder, profoundly impacts functional independence and participation. Virtual reality (VR) has developed as a potential neurorehabilitation tool, yet its therapeutic efficacy remains inconsistently validated. This overview aims to synthesize evidence from systematic reviews (SRs) and meta-analyses (MAs) to evaluate VR’s effectiveness in CP rehabilitation.MethodsSystematic searches across ten databases—Embase, Web of Science, Cochrane Library, PubMed, CINAHL, JBI, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), China Bio-Medical Literature Service System (Sino-Med), and Wanfang Database—identified SRs/MAs on VR for CP from inception to November 10, 2024. The duplicate rate of primary studies was assessed by calculating the corrected covered area (CCA) through the establishment of a literature overlap matrix. Methodological rigor, reporting quality, bias risk, and evidence quality were appraised using the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 (PRISMA2020), the Risk of Bias in Systematic Reviews (ROBIS), and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) tools, respectively.ResultsSixteen SRs/MAs (5 low quality, 11 very low quality, according to AMSTAR-2) were included. The CCA was calculated as 0.135, indicating a high degree of overlap. PRISMA 2020 compliance revealed incomplete reporting in 37% of items. ROBIS indicated low bias risk in 13 studies. GRADE assessments classified 58 outcomes: 9 moderate (15.5%), 21 low (36.2%), and 28 very low (48.3%) quality. VR demonstrated clinical potential for improving motor function and activities of daily living (ADL), particularly in younger children with higher intervention dosages. However, heterogeneity in outcome measures, CP subtypes, and VR protocols limited generalizability.ConclusionVR shows potential in improving motor dysfunction and ADL in CP. However, the included SRs/MAs typically exhibited low methodological and evidence quality. Therefore, caution must be taken when interpreting these findings. Moreover, high-quality randomized controlled trials and standardized VR protocols are urgently needed to establish evidence-based guidelines for CP rehabilitation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024614631, CRD42024614631.